The effects of task difficulty and presentation format on eye movements in risky choice - Zhang, Xiaomeng; Aimone, Jason A.; Alsharawy, Abdelaziz; Li, Flora; Ball, Sheryl; Smith, Alec (Frontiers in Behavioral Economics, 2024)
This study investigates the process of risky choice using eye tracking. We manipulate the complexity and presentation of lottery choices while measuring eye movements. In particular, we measure the frequencies of information collection procedures associated with established theories of risky choice, namely, expected utility theory and component comparison theory. These choice process patterns are sensitive to the difficulty of calculations and the presentation format of lotteries. Participants appear to transition between decision-making procedures depending on how lottery choices are presented and their complexity. They also attend to payoffs as the primary feature considered during component comparisons. Our findings emphasize the influence of information presentation on decision-making processes and decisions.